Clinical Relevance of Body Fluid Volume Status in Diabetic Patients With Macular Edema - Yao, Jie; Peng, Qingsheng; Li, Yuanhong; Liang, Anyi; Xie, Jianteng; Zhuang, Xuenan; Chen, Ruoyu; Chen, Yesheng; Wang, Zicheng; Zhang, Liang; Cao, Dan (Frontiers in Medicine, 2022)
Objective To investigate body fluid status in diabetic macular edema (DME) patients and the extent to which it is affected by renal function. Methods One hundred and thirty-two eyes from 132 patients with diabetes mellitus (DM) were prospectively collected in this cross-sectional, observational study. Thirty-five were DM patients without diabetic retinopathy (DR), 31 were DR patients without DME, and 66 were DME patients. The fluid status of each participant was quantified with extracellular water-to-total body water ratio (ECW/TBW) using a body composition monitor. Central subfield thickness (CST) and macular volume (MV) were obtained using optical coherence tomography (OCT). Urine albumin-to-creatinine ratio (UACR), estimated glomerular filtration rate (eGFR), and albumin was obtained using serum and urine laboratory data. Results ECW/TBW was significantly increased in DME patients (39.2 ± 0.9, %) compared to DM (38.1 ± 0.7, %, P = 0.003) and DR patients without DME (38.7 ± 0.9, %, P < 0.001). In multilinear regression, fluid overload was positively related to DME and UACR (DME vs. DM: β = 2.418, P < 0.001; DME vs. DR: β = 1.641, P = 0.001; UACR, per 102, β = 1.017, P = 0.01). In the binary logistic regression for DME risk, the area under the receiver operating characteristic curve (AUROC) increased significantly by adding ECW/TBW along with UACR and age (AUC: 0.826 vs. 0.768). Conclusion DME patients had elevated body fluid volume independent of kidney functions. The assessment of extracellular fluid status may help in the management of DME.